Genetic and Antigenic Analysis of Invasive Serogroup C Neisseria meningitidis in Canada: A Decrease in the Electrophoretic Type (Et)-15 Clonal Type and an Increase in the Proportion of Isolates Belonging to the Et-37 (But Not Et-15) Clonal Type During the Period from 2002 to 2009 - Jianwei Zhou; Frances Jamieson; Sharon Dolman; Linda MN Hoang; Prasad Rawte; Raymond SW Tsang (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Serogroup C meningococcal disease has been endemic in Canada since the early 1990s, with periods of hyperendemic disease documented in the past two decades. The present study characterized invasive serogroup C meningococci in Canada during the period from 2002 to 2009.